The use of industrial waste materials for alleviation of iron deficiency in sunflower and maize - Brigitta TÃ³th; Makoena Joyce Moloi (International Journal of Recycling of Organic Waste in Agriculture)
Purpose The aim of this study was to prove that the Fe-containing by-products (compost, sewage and lime sludge) have potential influence on the correction of Fe deficiency in sunflower and maize. Method The physiological parameters used were the dry matter (DM), the relative chlorophyll content, and the content of photosynthesis pigments (chlorophyll a, chlorophyll b and carotenoids). Results The results showed that sewage sludge was effective even when applied at low concentration (2 gLâ1) for both sunflower and maize plants. In maize, however, chlorophyll a was the only pigment induced after sewage sludge treatments in contrast to sunflower, which could be the reason for lower DM in maize. Compost could only be effective when applied at higher concentrations (4 gLâ1) for sunflower because of its low-Fe content, further showing that maize plants require more Fe. Despite its high-Fe content, lime sludge could not be effective in alleviating Fe deficiency for both sunflower and maize plants because of its high pH, which makes Fe unavailable for uptake by the plants. Conclusion Although the investigated by-products can be hazardous depending on their origin, their use as micro-element fertilizer can be a very economical way of utilization in the agricultural fields, which may limit the use of high quantities of expensive Fe-containing fertilizers. Among the three waste products, sewage sludge application proved to have a great potential of correcting Fe deficiency by inducing accumulation of the photosynthesis pigments, leading to high photosynthesis and eventually high DM.